2000
DOI: 10.1007/pl00011686
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of recurrence after curative resection of gastric carcinoma invading the muscularis propria: a multivariate analysis

Abstract: and early gastric cancer (EGC) as that confined to the mucosa or submucosa, regardless of the presence or absence of lymph node metastases. In Japan, the incidence of gastric cancer invading the muscularis propria (pm gastric cancer) accounts for about 10% of all patients with gastric cancer undergoing surgical resection [1,2]. The pm gastric cancer is usually treated by curative resection [3], and the 5-year survival rate for patients with pm gastric cancer was reported to be between 70% and 80%, a value betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
2
2
0
6
Order By: Relevance
“…In patients with risk factors for recurrence, postoperative treatment may be a reasonable option to improve the prognosis of gastric cancer. In gastric cancer, the two most common recurrence patterns are hematogenous recurrence, in relatively earlystage cancer [7,8,11,12] and peritoneal dissemination in advanced gastric cancer [4,13]. In the present study, peritoneal dissemination was observed in seven of the patients with recurrence (64%), with one each having hematogenous and mixed-type recurrence.…”
Section: Discussionsupporting
confidence: 50%
“…In patients with risk factors for recurrence, postoperative treatment may be a reasonable option to improve the prognosis of gastric cancer. In gastric cancer, the two most common recurrence patterns are hematogenous recurrence, in relatively earlystage cancer [7,8,11,12] and peritoneal dissemination in advanced gastric cancer [4,13]. In the present study, peritoneal dissemination was observed in seven of the patients with recurrence (64%), with one each having hematogenous and mixed-type recurrence.…”
Section: Discussionsupporting
confidence: 50%
“…However, our two cohorts had similar proportions of intestinal (66% US, 69% China) and diffuse (26% US and 29% China) tumors and similar distributions of well, moderate, and poorly differentiated histology, making them a good cohort for combined analysis. Recurrence rates in the US cohort were 2% (3/151) for T1a tumors, 7% (14/196) for T1b tumors, and 12% (8/67) for T2 tumors; quite similar to the rates in our Chinese cohort [T1a: 2% (4/209); T1b: 6% (12/187); T2: 14% (35/248)] and previous Eastern reports , which report recurrence rates ranging from 0.1% to 11.7% for T1a‐1bN0 patients, and 2.5% to 20.6% in T2N0 patients.…”
Section: Discussionsupporting
confidence: 88%
“…MP gastric cancer is usually treated by a curative surgical resection, and the 5-year survival rate was reported as 72% to 82% [3,4]. Although most patients with MP gastric cancer are cured by an R0 resection, 16% to 22% of these patients have recurrences postoperatively [3,5].There are many reports that the subclassifi cation of gastric cancer with invasion within the submucosal layer (SM gastric cancer) is useful to predict lymph node metastasis [6,7]. It remains unclear, however, whether subdivision of tumor invasion into the MP is useful for predicting lymph node metastasis and prognosis [8,9].…”
mentioning
confidence: 99%
“…MP gastric cancer is usually treated by a curative surgical resection, and the 5-year survival rate was reported as 72% to 82% [3,4]. Although most patients with MP gastric cancer are cured by an R0 resection, 16% to 22% of these patients have recurrences postoperatively [3,5].…”
mentioning
confidence: 99%